ANALISIS SPESIALISASI DAN KONSENTRASI SPASIAL INDUSTRI MANUFAKTUR DI INDONESIA TAHUN 2007-2013 - Cita Ayu Claudia (Program Studi Ekonomi Pembangunan, 2017)
Abstract the main objective of this research is to investigate manufakturing industries that specialize in several provinces in Indonesia and level of industry’s spatial concentration. In addition, this study also need to find the influencing factors of it. Using the specialization index analyst tool, it is known that there are only 12 types of sub-industries that are specialized in several provinces in Indonesia. besides by using the ratio concentration analysis tool known that the industry concentration is very high in the provinces of West Java, East Java, Central Java, and Banten. the results of the regression analysis show that : 1) competition index significantly and negatively related to concentration ratio which, if competetion index up to 1%, the concentration ratio would decreased amount 5.73E-06. 2) population density significantly and positively related to concentration ratio which, if population density up to 1%, the concentration ratio would increased amount 4.96E-07. 3) wage significantly and positively related to concentration ratio which, if wage up to1%, the concentration ratio would increased amount 0.004519Keyword : Linear Regression, Manufacturing Industry, Spatial Concentration, Specialization Industry